2016
DOI: 10.1007/s00436-016-5072-8
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and genotyping of Acanthamoeba strains (T4, T9, and T11) from amoebic keratitis patients in Iran

Abstract: The continuous increase in Acanthamoeba keratitis, a severe corneal infection, worldwide is mainly due to the increase in the number of soft contact lens users. In the present study, which involves a 5-year study, a total of 138 corneal scraps and contact lenses together with their paraphernalias were obtained from suspected amoebic keratitis patients. All samples were cultured using culture-enrichment method. Pathogenic assay, using thermotolerance and osmotolerance tests were also performed on the positive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 19 publications
3
21
1
Order By: Relevance
“…Acanthamoeba identification can be rapidly achieved using real-time molecular methods. For diagnostic purposes, the detection of Acanthamoeba at the genus level is sufficient to recognize whether an individual is infected [18,19]. A more precise differentiation of genotype is beneficial for better understanding of Acanthamoeba taxonomy and also facilitates the correct identification.…”
Section: Discussionmentioning
confidence: 99%
“…Acanthamoeba identification can be rapidly achieved using real-time molecular methods. For diagnostic purposes, the detection of Acanthamoeba at the genus level is sufficient to recognize whether an individual is infected [18,19]. A more precise differentiation of genotype is beneficial for better understanding of Acanthamoeba taxonomy and also facilitates the correct identification.…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen species of Acanthamoeba have been classified into three groups according to the shape and size of cysts. Species in group I are nonpathogenic except A. astronyxis , A. byersi and A. comandoni [ 22 , 23 ]. Most of the pathogenic Acanthamoeba species belong to group II.…”
Section: Discussionmentioning
confidence: 99%
“…In Iran, different Acanthamoeba was isolated from soil and water resources in different areas. The isolates belonged to different genotypes especially T4 [ 12 ]. A research was conducted by Armand et al showed that the most prevalent genotype of Acanthamoeba in Shiraz water supplies is T4 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PCR reaction was performed using JDP primers including JDP1 5′-GGCCCAGAT CGTTTACCGTGAA-3′ and JDP2 5′- TCTCACAAGCTGCTAGGGGAGTCA-3 [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation